Seasonal Variations of Heavy Metals Concentrations in Water and Histopathological Evaluation of Tilapia Fish (Orechromis Mosambicus) Harvested from Gusau, Kaura -Namoda and Mafara Dams, Zamfara State, Nigeria - M. Sunday; B. S. Bara'u; C. Odenigbo (Journal of Applied Sciences and Environmental Management)
The objective of this paper was to investigate the seasonal variation of heavy metal concentration in water and histopathological evaluation of tilapia fish (Orechromis  mosambicus) harvested from Gusau, Kaura-Namoda, Tsafe and Talata Mafara dams in Zamfara state, Nigeria using appropriate standard procedures. Results obtained showed that the concentrations [mg/l] of Pb in the Dams were 0.0038±0.64 (Gusau dam); 0.0069±0.23 (Kaura-Namoda dam); 0.0057±0.89 (Tsafe dam), 0.0076±0.75 (Talata Mafara Dam) during the rainy season and 0.0067±0.67(Gusau dam); 0.124±0.88 (Kaura-Namoda dam); 0.1678±0.93 (Tsafe dam), 0.1563±0.07(Talata Mafara Dam) for the dry season respectively. The result revealed a spatial and non-uniform distribution in the concentration of the heavy metals (Zn, Cd, Cr, Pb and Fe) in the water, in all locations studied. The concentrations of heavy metal are generally higher during the dry season than in the wet season. Zn and Cr levels were within international safe limits while Cd, Pb levels were far above the WHO and USEPA limits. The histology assessment of tissues such as gills, liver and skin (muscle) showed that most common gill abnormalities observed in the fish sample inhabited in all the locations have desquamation of lamellar epithelium, hypertrophy of epithelial cells, lifting up of lamellar epithelium, intraepithelial oedema, aneurysm, hyperplasia, and haemorrhage in the gill filament. Histology of liver revealed the presence of heterogeneous parenchyma characterized by vacuolization, foci of necrosis, hypertrophy of nuclei and degenerated hepatocytes. Histology changes of the skin (muscle) were mostly at the level of the epidermis, without major changes in the dermis and hypodermis.